Pelatihan Manajemen Usaha dalam Meningkatkan Usaha UMKM Rumah Makan Kartika - Ni Ketut Cantika Paraswani; Kadek Dena Krisnantara; Nyoman Sulasmi; Mertyani Sari Dewi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to identify culinary tourism that can be developed in Buleleng Regency. This research method is a study of field observation documentation and interviews. The object of this research is one of the restaurants located in Singaraja, namely Kartika Restaurant. Kartika restaurant is a restaurant that has been around since 1965 with the concept of a Chinese Food restaurant. In this research activity, the researcher found several problems, namely in the fields of production, marketing and finance. So from this problem the researchers provided some training to Kartika Restaurant. The training provided is training on making logos, promotion through social media, and making simple bookkeeping. So from this research, the Kartika Restaurant MSMEs become more aware of the importance of logos in a product, the importance of recording finances regularly, and also how to sell through social media.